Aminotransferase-to-lymphocyte ratio as a valuable prognostic marker for patients with stage I-III colorectal cancer: a retrospective study - Xie, Hailun; Wei, Lishuang; Tang, Shuangyi; Gan, Jialiang (Frontiers in Oncology, 2024)
BackgroundThere are no population-based studies on the prognostic value of the preoperative aminotransferase-to-lymphocyte ratio (AALR) in predicting recurrence and survival in patients with colorectal cancer (CRC) who have undergone curative resection.AimThis study explored the relationship between AALR and prognosis of CRC patients, specifically stage III CRC.MethodsRestricted Cubic Splines were used to evaluate the relationship between AALR and outcomes. The survival curve was generated using the Kaplan-Meier method and the log-rank test. COX regression analysis was used to identify the independent prognostic factors of CRC patients. Logistic regression analysis was used to assess the independent risk factors affecting sarcopenia and postoperative complications. Concordance index and calibration curves were used to evaluate the discriminative ability of the prognostic nomograms. Finally, according to a ratio of 7:3, the total population was randomized into two cohorts to validate the practicability of the prognostic nomograms.ResultsIn total, 1304 stage I-III CRC were enrolled in this study. There was a significant positive correlation between AALR and PFS/OS in CRC patients. The PFS/OS ratio of the high AALR group was significantly lower than that of the low AALR group. In the subgroup analysis, we found that the AALR significantly stratified the prognosis of patients with stage III CRC. A high AALR was still independently associated with poor PFS (HR = 1.335, 95% CI =1.075–1.657, p=0.009) and OS (HR = 1.382, 95% CI =1.139–1.677, p=0.001) in CRC patients. Variables with a value ≤ 0.05 in multivariable analysis were incorporated into the construction of prognostic nomograms for predicting 1-5 years PFS/OS of CRC patients. The results of the concordance index and calibration curves confirmed that these prognostic nomograms had a good prediction accuracy. In addition, we demonstrated the good predictive performance of these nomograms in a randomized internal validation cohort.ConclusionAALR is an effective prognostic marker for predicting long-term outcomes and could provide a valuable reference for sarcopenia and postoperative complications in CRC patients. AALR-based nomograms have good predictive accuracy and can help to develop individualized risk stratification, follow-up, and treatment strategies for CRC patients.